2020
DOI: 10.1002/mde.3152
|View full text |Cite
|
Sign up to set email alerts
|

Customizing competitive strategy to entry timing: Implications for firm performance in the pharmaceutical industry

Abstract: Our study examines the effect of business‐level strategy on performance. Past literature examining the aforementioned effect in the pharmaceutical industry is scarce. Furthermore, there is a lack of studies that analyze how competitive strategy is contingent on firm entry timing. Hence, to explore our understanding in this area, the present study was conducted in the German pharmaceutical industry. Two hundred valid responses were collected from CEOs. The data were analyzed using SPSS and partial least square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The studies by Kustiningsih and Tjahjadi (2020), Gonz alez-Rodr ıguez et al (2018), Chen et al, (2017) and Banker et al (2014) revealed that strategies have a positive impact on performance. However, other studies (Castillo-Apraiz and Matey, 2020;Gorondutse and Hilman, 2019) have revealed that strategy has no effect on performance. This gap justifies further study.…”
Section: Pms Influence On Strategy Pillars: Opp Relationshipmentioning
confidence: 91%
“…The studies by Kustiningsih and Tjahjadi (2020), Gonz alez-Rodr ıguez et al (2018), Chen et al, (2017) and Banker et al (2014) revealed that strategies have a positive impact on performance. However, other studies (Castillo-Apraiz and Matey, 2020;Gorondutse and Hilman, 2019) have revealed that strategy has no effect on performance. This gap justifies further study.…”
Section: Pms Influence On Strategy Pillars: Opp Relationshipmentioning
confidence: 91%
“…The industries and proportions of the surveyed companies quantify the structural correlation between independent structures and provides a robust analysis (Hair et al, 2014). At present, the SEM method has been widely used in sociology, management, economics and other fields (Castillo-Apraiz & Matey, 2020;Hair et al, 2011;He et al, 2011;Mu et al, 2016;Wang et al, 2017) and has been well applied. Its advantage is that it can deal with multiple dependent variables at the same time.…”
Section: Sem Checkingmentioning
confidence: 99%